Impact of sector-based upgrading on home-based enterprises: a case study of Chaisa Settlement. (October 2017) - Mpembamoto, Kelvin; Nchito, Wilma; Siame, Gilbert; Wragg, Emma
While upgrading approaches have evolved over the years, and often include a focus on improving the livelihoods of people living in informal settlements, there remains little attention or understanding in the literature of how upgrading can influence the livelihoods of residents in informal settlements. This paper examines the extent to which upgrading can contribute to improvement in economic activities, looking specifically at the case of the Chaisa settlement in Zambia, where various upgrading projects were conducted in recent years. It investigates the extent to which this upgrading has contributed to the establishment and expansion of such home-based enterprises as shops, kiosks, saloons and barbershops, as well as its impact on room renting and on livelihoods generally, and discusses the dynamics underlying these improvements.